1986
DOI: 10.1128/jcm.24.4.684-685.1986
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteric parasites in homosexual patients attending an outpatient clinic

Abstract: A total of 372 pooled stool specimens from 274 homosexual men with diarrhea were submitted for parasitologic examination over a 2.5-year period. Each two-vial pooled specimen set contained portions of stool from 3 consecutive days in Formalin and polyvinyl alcohol. Of the 274 patients, 133 (48.5%) harbored one or more intestinal protozoa, with 161 (43.3%) of the 372 specimens submitted being positive for one or more organisms. The parasites identified included Entamoeba histolytica (71 patients), Giardia lambl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Inversely, some studies failed to detect Dientamoeba in the stools of HIV infected patients with or without GI complaints. [83][84][85] Peters et al 86 found that over 1% of homosexual men with diarrhea (regardless of HIV status) carried Dientamoeba. Lainson and da Silva 87 reported Dientamoeba in 1/34 HIV infected individuals.…”
Section: Dientamoeba and Hiv Infectionmentioning
confidence: 99%
“…Inversely, some studies failed to detect Dientamoeba in the stools of HIV infected patients with or without GI complaints. [83][84][85] Peters et al 86 found that over 1% of homosexual men with diarrhea (regardless of HIV status) carried Dientamoeba. Lainson and da Silva 87 reported Dientamoeba in 1/34 HIV infected individuals.…”
Section: Dientamoeba and Hiv Infectionmentioning
confidence: 99%
“…High rates of enteric protozoan parasitism have been reported among men who have sex with men (MSM) in metropolitan areas throughout the world. [1][2][3] Sexual activity has been shown to be the primary mode of transmission for several important parasitic diseases and has resulted in a significant prevalence of enteric parasitic infections among male homosexuals. 4 Furthermore, the association between intracellular intestinal parasites and infection with human immunodeficiency virus (HIV) is well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Previous documented prevalence rates of enteric protozoa in MSM include 48.5% in the United States, 50.6% in mainland China, 57% in the United Kingdom, and 81% in a 128 Australian homosexual males. 1,[3][4][5] Intestinal parasitosis is an important health problem affecting people in both developing and developed regions of the world. Although this is usually self-limiting and almost invariably non-fatal, it results in significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Among immunocompromised patients, for example those with HIV, certain risk behaviors, such as homosexual relations and practicing oro-anal sex, can exacerbate the possibility of acquiring some intestinal parasitoses such as giardiasis, cryptosporidiosis and strongyloidiasis, where the symptomatic pictures are more serious than those of individuals with a non-compromised immune system [11,12]. Keystone and et al (1980) [13] demonstrated, even before the discovery of AIDS, the greater risk for infection by intestinal parasites through these risk behaviors when comparing the prevalence of enteroparasites between groups of heterosexual and homosexual males.…”
mentioning
confidence: 99%